The potential of betle leaf (Piper betle L.) against Staphylococcus aureus to cure mastitis: A systematic review - Jannata, Rahma Winahyu; Prihantono, Prihantono; Idris, Irfan (Babali Nursing Research, 2023)
Mastitis is a problem in breastfeeding causes nutritional deficiencies in the baby. Staphylococcus aureus is one of the bacteria that causes mastitis. Betle leaf (Piper betle L.) has been used in several health problems and has antimicrobial activity. This study aims to explore the potential of betel leaf (Piper betle l.) against Staphylococcus aureus to cure mastitis. A systematic review was carried out according to the PRISMA guidelines. Searches were conducted in three databases namely PubMed, Google Scholar, and Science Direct. Search using keywords according to the Mesh term, namely 'betle leaf (Piper betle l.)', 'Staphylococcus aureus' and 'Mastitis'. 198 articles were found in a database search. 8 studies were analyzed. All studies found that both types of pipers betle, both green and red, showed positive effects in the treatment of mastitis. Processing techniques, storage, and certain concentrations such as boiling temperature affect the optimum inhibition zone of bacteria. The addition of certain formulas also increases the antimicrobial activity. The use of antibiotics and betel leaf extract can be used simultaneously to treat mastitis. Betle leaf (Piper betle L.), has a positive effect on the management of mastitis, but processing techniques, concentrations, and adjuvants need to be studied further.